Turkish Sufi Organizations and The Development of Islamic Education in Indonesia - Firdaus Wajdi (Analisa: Journal of Social Science and Religion, 2020)
Sufism has contributed substantially in the development of Islam across the globe. It is also the case of Indonesia. Sufi preachers have been noticed as among the early Muslims who conveyed and disseminate Islam in the Archipelago. This trend seems to be repeated in this current Indonesian Islam. However, what is commonly unknown, Turkish organization also takes part in this current mode. Particularly, it is with the Islamic transnational organization from Turkey operating in Indonesia as the actors. This article aims at discussing the Sufi elements within three Turkish based transnational communities in Indonesian Islam and their contribution to Islamic education as part of Islamic development in the current Indonesia. This is a qualitative research to the topics within the three Turkish origin transnational Islamic organizations, namely the Jamaat Nur, the Fethullah Gülen Affiliated Movement, and the Suleymaniyah. This article will then argue that Sufism has continued to be one of the contributing factors for the development of Islam and in relation to that the Sufi elements within the three Turkish Transnational organizations also contribute to their acceptance in Indonesia. Overall, the Sufi elements have shaped the image and identity of the Turkish Muslims in developing the Islamic studies in Indonesia.